Flexible Thermoelectric Polymer Composites Based on a Carbon Nanotubes Forest. (29th July 2018) - Yusupov, Khabib; Stumpf, Steffi; You, Shujie; Bogach, Aleksei; Martinez, Patricia M.; Zakhidov, Anvar; Schubert, Ulrich S.; Khovaylo, Vladimir; Vomiero, Alberto
Abstract: Polymer‐based composites are of high interest in the field of thermoelectric (TE) materials because of their properties: abundance, low thermal conductivity, and nontoxicity. In applications, like TE for wearable energy harvesting, where low operating temperatures are required, polymer composites demonstrate compatible with the targeted specifications. The main challenge is reaching high TE efficiency. Fillers and chemical treatments can be used to enhance TE performance of the polymer matrix. The combined application of vertically aligned carbon nanotubes forest (VA‐CNTF) is demonstrated as fillers and chemical post‐treatment to obtain high‐efficiency TE composites, by dispersing VA‐CNTF into a poly (3, 4‐ethylenedioxythiophene) polystyrene sulfonate matrix. The VA‐CNTF keeps the functional properties even in flexible substrates. The morphology, structure, composition, and functional features of the composites are thoroughly investigated. A dramatic increase of power factor is observed at the lowest operating temperature difference ever reported. The highest Seebeck coefficient and electrical conductivity are 58.7 µV K −1 and 1131 S cm −1, respectively. The highest power factor after treatment is twice as high in untreated samples. The results demonstrate the potential for the combined application of VA‐CNTF and chemical post‐treatment, in boosting the TE properties of composite polymers toward the development of high efficiency, low‐temperature, flexible TEs. Abstract : Flexible thermoelectric polymer composites are developed, based on vertically aligned carbon nanotubes forest and chemical post‐treatment. The thermoelectric properties of the composites are improved, thanks to the preferential electric conduction of the aligned carbon nanotubes and the chemical modification of the polymer matrix. The composite system is stable under bending, paving the way for the development of flexible hybrid thermoelectrics.